Persistent, generalized hypersensitivity of olfactory bulb interneurons after olfactory fear generalization - Kass, Marley D. (Neurobiol Learn Mem, 2017)
Generalization of fear from previously threatening stimuli to novel but related stimuli can be beneficial, but if fear overgeneralizes to inappropriate situations it can produce maladaptive behaviors and contribute to pathological anxiety. Appropriate fear learning can selectively facilitate early sensory processing of threat-predictive stimuli, but it is unknown if fear generalization has similarly generalized neurosensory consequences. We performed in vivo optical neurophysiology to visualize odor-evoked neural activity in populations of periglomerular interneurons in the olfactory bulb 1 day before, 1 day after, and 1 month after each mouse underwent an olfactory fear conditioning paradigm designed to promote generalized fear of odors. Behavioral and neurophysiological changes were assessed in response to a panel of odors that varied in similarity to the threat-predictive odor at each time point. After conditioning, all odors evoked similar levels of freezing behavior, regardless of similarity to the threat-predictive odor. Freezing significantly correlated with large changes in odor-evoked periglomerular cell activity, including a robust, generalized facilitation of the response to all odors, broadened odor tuning, and increased neural responses to lower odor concentrations. These generalized effects occurred within 24 hours of a single conditioning session, persisted for at least 1 month, and were detectable even in the first moments of the brain’s response to odors. The finding that generalized fear includes altered early sensory processing of not only the threat-predictive stimulus but also novel though categorically-similar stimuli may have important implications for the etiology and treatment of anxiety disorders with sensory sequelae.